Ir. Dr. Chin Siew Choo produces sustainable construction material OHE-Crete - Hafizatulazlin, Abdul Aziz; Nur Hartini, Mohd Hatta (2020)
A researcher from the Department of Civil Engineering, College of Engineering, Universiti Malaysia Pahang (UMP), Ir. Dr. Chin Siew Choo produced sustainable construction material, namely OHE-Crete.